Cerebral Organoids and Antisense Oligonucleotide Therapeutics: Challenges and Opportunities - Lange, Jenny; Zhou, Haiyan; McTague, Amy (Frontiers in Molecular Neuroscience, 2022)
The advent of stem cell-derived cerebral organoids has already advanced our understanding of disease mechanisms in neurological diseases. Despite this, many remain without effective treatments, resulting in significant personal and societal health burden. Antisense oligonucleotides (ASOs) are one of the most widely used approaches for targeting RNA and modifying gene expression, with significant advancements in clinical trials for epilepsy, neuromuscular disorders and other neurological conditions. ASOs have further potential to address the unmet need in other neurological diseases for novel therapies which directly target the causative genes, allowing precision treatment. Induced pluripotent stem cell (iPSC) derived cerebral organoids represent an ideal platform in which to evaluate novel ASO therapies. In patient-derived organoids, disease-causing mutations can be studied in the native genetic milieu, opening the door to test personalized ASO therapies and n-of-1 approaches. In addition, CRISPR-Cas9 can be used to generate isogenic iPSCs to assess the effects of ASOs, by either creating disease-specific mutations or correcting available disease iPSC lines. Currently, ASO therapies face a number of challenges to wider translation, including insufficient uptake by distinct and preferential cell types in central nervous system and inability to cross the blood brain barrier necessitating intrathecal administration. Cerebral organoids provide a practical model to address and improve these limitations. In this review we will address the current use of organoids to test ASO therapies, opportunities for future applications and challenges including those inherent to cerebral organoids, issues with organoid transfection and choice of appropriate read-outs.